Barnamordsärenden i Finland på 1800-talet: Bevisning och kvinnornas försvarsstrategier - Ervasti, Kaijus (Nordisk Tidsskrift for Kriminalvidenskab, 1997)
The article is relating to the history of law and deals with infanticides in Finland in the 19th century based on statistics and trial records. Special attention has been paid to the facts; what kind of evidence convicted the women, and how did they try to defend themselves in the courts. Resource material used in this article are the infanticide cases of the years 1820, 1840, 1860 and 1880 which have been tried by the Justice Department of the Senate (Supreme Court).